An Efficient Voltammetric Sensor Based on Graphene Oxide-Decorated Binary Transition Metal Oxides Bi2O3/MnO2 for Trace Determination of Lead Ions - Guangli Li; Xiaoman Qi; Yang Xiao; Yuchi Zhao; Kanghua Li; Yonghui Xia; Xuan Wan; Jingtao Wu; Chun Yang (Nanomaterials, 2022)
Herein we present a facile synthesis of the graphene oxide-decorated binary transition metal oxides of Bi2O3 and MnO2 nanocomposites (Bi2O3/MnO2/GO) and their applications in the voltammetric detection of lead ions (Pb2+) in water samples. The surface morphologies, crystal structures, electroactive surface area, and charge transferred resistance of the Bi2O3/MnO2/GO nanocomposites were investigated through the scanning electron microscopy (SEM), power X-ray diffraction (XRD), cyclic voltammetry (CV), and electrochemical impedance spectroscopy (EIS) techniques, respectively. The Bi2O3/MnO2/GO nanocomposites were further decorated onto the surface of a glassy carbon electrode (GCE), and Pb2+ was quantitatively analyzed by using square-wave anodic stripping voltammetry (SWASV). We explored the effect of the analytical parameters, including deposition potential, deposition time, and solution pH, on the stripping peak current of Pb2+. The Bi2O3/MnO2/GO nanocomposites enlarged the electroactive surface area and reduced the charge transferred resistance by significant amounts. Moreover, the synergistic enhancement effect of MnO2, Bi2O3 and GO endowed Bi2O3/MnO2/GO/GCE with extraordinary electrocatalytic activity toward Pb2+ stripping. Under optimal conditions, the Bi2O3/MnO2/GO/GCE showed a broad linear detection range (0.01–10 μM) toward Pb2+ detection, with a low limit of detection (LOD, 2.0 nM). The proposed Bi2O3/MnO2/GO/GCE electrode achieved an accurate detection of Pb2+ in water with good recoveries (95.5–105%).